Giant Molluscum Contagiosum in an Infant - Kazez, Ahmet; Kökçam, İbrahim; Yekeler, Hayreddin (Fırat University, 2002)
Giant molluscum contagiosum is a rare lesion, whereas classical disseminated type of it is common in children. An 11-month-old male infant was determined to have a giant molluscum contagiosum on the left side of his neck. Scalp, eyelids and sole are the most commonly sites of giant lesions. It was totally excised and histopathological examination confirmed the diagnosis. In this report we presented a very rarely seen giant molluscum contagiosum in an unusual localisation in an infant.

Molluskum kontagiyozum' un klasik tipi çocuklarda sık görülmesine rağmen, dev formu nadirdir. Onbir aylık bir erkek çocukta boynunun sol ön kısmında dev bir molluskum kontagiyozum tesbit edildi. Dev lezyonların en sık yerleşim yeri saçlı deri, göz kapağı ve ayak tabanıdır. Total olarak çıkarılan lezyonun histopatolojik incelemesi tanıyı kesinleştirdi. Bu makalede, bebeklik döneminde atipik yerleşim gösteren dev molluskum kontagiyozum olgusu nadir görülmesi nedeni ile sunuldu.
BEBEKTE DEV MOLLUSKUM KONTAGİYOZUM